Flexural buckling of circular concrete-filled stainless steel tubular columns. (May 2020) - Hassanein, M.F.; Shao, Yong-Bo; Elchalakani, M.; El Hadidy, A.M.
Abstract: Concrete-filled steel tubular (CFST) columns are currently used in offshore structures and oil and gas drilling platforms, from which the external steel tubes become at risk due to the aggressive ocean climate and/or sea water. Therefore, the CFST columns in corrosive environment lose their excellent mechanical performances and safety as the thicknesses of steel tubes decrease due to corrosion. This has recently led to the introduction of the concrete-filled stainless steel tubular (CFSST) columns, which benefit from the stainless steel as a superior metallic corrosion resistant material. Accordingly, CFSST short columns have recently attracted the scientific community. However, circular CFSST slender columns have received very little attention. Currently, this paper provides a nonlinear finite element (FE) inelastic analysis for the axially-loaded circular CFSST slender columns to substitute the lack in their behaviour; especially when the relative cheap lean duplex stainless steel material (EN 1.4162) is utilised. The FE models are firstly validated by using the available test results in literature. This validation stage is, then, followed by a parametric analysis to explore the fundamental behaviour of such columns considering the most important factors. The paper divides the slender columns into intermediate length and long columns based on the type of the overall buckling that takes place, and then the behavioural differences between both types are clearly addressed. The obtained FE axial strengths are additionally compared with those predicted by the European (EC4) and American (AISC) specifications. Based on these comparisons, a formula, based on Eurocode 4, is suggested for the routine compressive design practice of these columns, which is found to fit well with the axial strengths of current slender columns which utilise the lean duplex stainless steel material. Highlights: A finite element model for CFSST slender columns under axial loading is presented. Using ABAQUS, 3D FE models for CFSSTs under axial compression are developed. Behavioural differences between intermediate length and long columns are addressed. The proposed design model is shown to predict well the strengths of CFSST columns.